CORRELATION AMONG GRAMMAR MASTERY AND VOCABULARY SIZE TOWARD TRANSLATION ABILITY ON REPORT TEXT - Husna, Fuyudhatul; Widiastuty, Hesty; Sugianto, Aris (IKIP Siliwangi, 2021)
The crucial problem of translating Indonesia to English language are the students’ lack of knowledge and mother tongue (source language) that two of them are grammar and vocabulary. The researcher focused to measure the correlation among grammar mastery and vocabulary size toward translation ability on report text at seventh semester students in State Islamic Institute of Palangka Raya that use quantitative method with a correlational design. The researcher’s instruments were three test which were grammar mastery, vocabulary size, and translation test that were tested to the 32 students’ translation class in academic year 2017/2018. The numerical data were analyzed by Pearson Product Moment that showed that: (1) the most students got “fail” (43.75%) grammar mastery, (2) the most students got “excellent” (46.875%) vocabulary size, (3) the most students got “enough” (87.5%) translation ability. The significant correlation among three variables were proved by correlation coefficient 0.604 (strong category), Fchange > Ftable = 8.349 > 3.33, and the contribution of grammar mastery and vocabulary size delivered 36.5%. Thus, it sums that students’ grammar mastery and vocabulary size correlate with the quality of students’ translation ability on report text at seventh semester students in academic year 2017/2018. Keywords: Grammar Mastery, Vocabulary, Translation